Gadget, Parenting Style, Work Stress, and Toddler Speech Delay:A Retrospective Analysis in Industrial Area of Bekasi - Anom Dwi Prakoso; Ice Marini (Journal of Maternal and Child Health, 2025)
Background: Speech delay affects around 20% of toddlers in Indonesia and is prevalent in industrial areas where parents face long working hours. This study aimed to analyze the relationship of screen time, parenting style, and parental work stress with speech delay in toddlers.Subjects and Method: This retrospective case-control study was conducted in Bekasi industrial area, August- September 2025. A total of 60 toddlers (13 with speech delay, 47 controls) were selected purposively. Speech delay was diagnosed using Denver II and MacArthur-Bates CDI. Inde¬pendent variables included screen time, parenting style, and work stress, measured with validated questionnaires. Data were analyzed using Chi-square and logistic regression.    Results: The prevalence of speech delay was 21.7%. Screen time >1 hour/day was significantly associated with a higher risk of speech delay (OR=13.61; 95% CI=3.21 to 28.94; p=0.002). High parental work stress also increased the risk (OR=10.84; 95% CI=2.13 to 21.77; p=0.013). Parenting style showed no significant association (OR=2.73; p=0.233). Qualitative analysis revealed six themes including digital parenting, alternative stimulation, interactions that limit work stress, responsive vs. permissive parenting, awareness and intervention, and socioeconomic influences.Conclusion: Excessive screen time and parental work stress are dominant risk factors for toddler speech delay in industrial families. Prevention efforts should focus on digital literacy for parents, responsive parenting, and stress management programs at community and workplace levels.